If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 2y = 90 Solving 9x + 2y = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 9x + 2y + -2y = 90 + -2y Combine like terms: 2y + -2y = 0 9x + 0 = 90 + -2y 9x = 90 + -2y Divide each side by '9'. x = 10 + -0.2222222222y Simplifying x = 10 + -0.2222222222y
| -307=6b+-7(-5b+-3) | | t^2-9t+18= | | -(1+8p)-6p=-3p-23 | | (5/6)x=5 | | (3-i)-(-4+9i)= | | 6m+-6(7+-3m)=102 | | -9/.6 | | -9/3/5 | | 15h=10h+80 | | 6z+11=59 | | (2x)(2x)=x+20 | | 5/5*2(6-2) | | 4+logx=10 | | 6x=330 | | 6x=10y+60 | | 15y^3-35y^2-30y= | | -7(x)=7 | | 7(x)=-7 | | u/-3=-4.2 | | s/2=3.02 | | b-2=5.9 | | (0.3x+0.6)=1.44 | | y+3.43=18.63 | | 4y^2+8y+16=0 | | c/-2=0.43 | | c-9.77=3.9 | | 20x=24x+8 | | 0.93=-p | | 20p=-16 | | -704=16m | | c/-16=24 | | n/18=-26 |